Identification of Organizational Factors Affecting the Deployment of E-learning System in Islamic Azad University Tehran Medical Sciences Branch - Mirsaidi, Golnoosh; Imani, Mohammad Naghi; Nazem, Fattah (International Review of Management and Marketing, 2017)
The growing desire and demand for university education and the ever-increasing attention paid to education in Iran on the one hand, and the attractions and capabilities of web-based training on the other, have brought e-learning into focus. E-learning can make it possible for university students to use new knowledge, and medical faculties are based on the use of such skills and knowledge. The present paper aimed to identify organizational factors affecting the evaluation of e-learning in the Islamic Azad University of Medical Sciences, Tehran. The statistical population included all faculty members of the Islamic Azad University of Medical Sciences, Tehran. In order to achieve the research objectives, the mixed methods research was used. In the qualitative part, study findings indicate that organizational factors affecting the deployment of e-learning in universities include economic, technological, and administrative-logistic factors. Results of the confirmatory analysis of the model suggest the suitability of factor loadings of markers (items) related to each component in the prediction of the capacities of economic, technological, and administrative-logistic dimensions, and the suitability of the factor loading of each component as the marker of economic, technological, and administrative-logistic dimensions of the feasibility assessment of e-learning deployment in the prediction of this variable. Results of the evaluation of the current status of the Islamic Azad University of Medical Sciences, Tehran, in terms of the identified organizational factors showed that the technological dimension of the feasibility assessment of e-learning deployment is significant, positive, and in a favorable condition (t=6.656, p=0.001), while the administrative-logistic (t=-0.339) and economic (t=0.685) dimensions are not significant or in a good status for the deployment of e-learning. Keywords: Organizational; Economic; Technological; Administrative; Logistic factors; E-learning; University JEL Classifications: L2, L91